Ricky Ricotta's mighty robot vs. the Jurassic Jackrabbits from Jupiter : the fifth robot adventure novel - Pilkey, Dav, 1966-; Ontiveros, Martin (New York : Scholastic, 2002)
General Jackrabbit and his Robo-Rabbits from Jupiter attempt to take over the world on Ricky Ricotta's birthday.
School Library Journal, December 2002.
Horn Book, April 2003.
Teacher Librarian, April 2003.
Library Media Connection, April 2003.
4.0
K-3
Keywords: Ricotta, Ricky (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Robots -- Juvenile fiction; Heroes -- Juvenile fiction; Ricotta, Ricky (Fictitious character) -- Fiction; Mice -- Fiction; Robots -- Fiction; Heroes -- Fiction; Humorous stories; Ricotta, Ricky (Fictional character) -- Fiction; Mice -- Fiction; Robots -- Fiction; Heroes and heroines -- Fiction; Humorous fiction; Mice -- Fiction; Robots -- Fiction; Heroes -- Fiction; Humorous stories; Cartoons and comics -- Fiction; Humorous fiction